Assessment of soil surface scarification and reseeding with sulla (Hedysarum coronarium L.) of degraded Mediterranean semi-arid rangelands - Slim, Slim; Louhaichi, Mounir; Gamoun, Mouldi; Ates, Serkan; Hassan, Sawsan; Rhomdhane, Oumeima; Ouled Belgacem, Azaiez (Taylor and Francis, 2025)
Climate change and degradation of natural resources pose daunting challenges in arid and semi-arid rangelands of southern Mediterranean region. Overcoming these challenges requires considerable management actions efforts. In this context, the current two-year (2017/2018 and 2018/2019) study investigated the effects of soil surface scarification and reseeding of rangelands with sulla (Hedysarum coronarium L.) on botanical composition, biomass production, water productivity and pastoral value in the Sbaihia community, Tunisia. The experimental design consisted of a randomised complete block design with six replications. The treatments were: (i) soil surface superficial scarification; (ii) reseeding sulla following soil scarification; and, (iii) control. Despite the relatively important interannual variation, the highest aboveground net primary production (2 307 and 5 330 kg dry matter ha−1), water productivity (9.5 and 11.8 kg DM mm−1), and pastoral value (2 099 and 4 853 forage units ha−1) values were recorded in the rangelands reseeded with sulla in both growing seasons. Sulla contribution in the species composition of reseeded rangelands increased from 1.7% in 2018 to 2% in 2019. Although soil surface scarification increased the vegetation cover, its effect on biomass production was not significant. Therefore, combined soil scarification and reseeding well-adapted native forage species has a great potential to improve productivity of semi-arid rangelands.